2021
DOI: 10.1007/s10534-021-00313-0
|View full text |Cite
|
Sign up to set email alerts
|

Anticancer effects against colorectal cancer models of chloro(triethylphosphine)gold(I) encapsulated in PLGA–PEG nanoparticles

Abstract: Chloro(triethylphosphine)gold(I), (Et3PAuCl hereafter), is an Auranofin (AF)-related compound showing very similar biological and pharmacological properties. Like AF, Et3PAuCl exhibits potent antiproliferative properties in vitro toward a variety of cancer cell lines and is a promising anticancer drug candidate. We wondered whether Et3PAuCl encapsulation might lead to an improved pharmacological profile also considering the likely reduction of unwanted side-reactions that are responsible for adverse effects an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 29 publications
(52 reference statements)
0
19
0
Order By: Relevance
“…Recently, it was reported that auranofin alone or in combination with other drugs targeting TrxR can induce apoptosis through inhibition of the AKT pathway [ 29 , 52 , 53 , 54 , 55 ]. Similarly, the AKT pathway has been proven to take part in the apoptotic cell death induced by the auranofin-related compound chloro(triethylphosphine)gold(I) [ 56 ] and an N-heterocyclic carbene–gold(I) complex [ 57 ]. In accordance with this evidence, we demonstrated that Au 2 phen, Auoxo6, and AuL12 possess the ability to downregulate the phosphorylation of AKT, thereby suggesting an important role of the AKT pathway in regulating gold(III)-induced cell death.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it was reported that auranofin alone or in combination with other drugs targeting TrxR can induce apoptosis through inhibition of the AKT pathway [ 29 , 52 , 53 , 54 , 55 ]. Similarly, the AKT pathway has been proven to take part in the apoptotic cell death induced by the auranofin-related compound chloro(triethylphosphine)gold(I) [ 56 ] and an N-heterocyclic carbene–gold(I) complex [ 57 ]. In accordance with this evidence, we demonstrated that Au 2 phen, Auoxo6, and AuL12 possess the ability to downregulate the phosphorylation of AKT, thereby suggesting an important role of the AKT pathway in regulating gold(III)-induced cell death.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, a few studies in the recent literature suggest new valuable strategies to improve the pharmacological profiles of AF and its analogs. We refer specifically to a couple of studies that delineate feasible strategies for therapeutic intervention [ 43 , 56 ] . In a first study, encapsulation of Et 3 PAuCl in PLGA nanoparticles proved to bring about some favorable pharmacological effects such as retention of the cytotoxic activity, attenuation of the general reactivity of the gold center, and expected reduction of the drug’s adverse effects.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, various research groups have found that auranofin [ 35 , 36 ] , beyond its known anti-inflammatory actions, also exhibits prominent anticancer, antibacterial, and antiparasitic properties [ 37 - 43 ] . Accordingly, during the past few years, auranofin has attracted a lot of attention in the medicinal chemistry scientific community as a prospective anticancer and anti-infective agent on the ground of drug repurposing strategies.…”
Section: Auranofin and Its Analogs As Anticancer Agents: Chemico-biol...mentioning
confidence: 99%
See 2 more Smart Citations